2017
DOI: 10.1038/npp.2017.67
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Dopamine Synthesis Capacity in Schizophrenia and Striatal Blood Flow Change During Antipsychotic Treatment and Medication-Free Conditions

Abstract: Standard-of-care biological treatment of schizophrenia remains dependent upon antipsychotic medications, which demonstrate D receptor affinity and elicit variable, partial clinical responses via neural mechanisms that are not entirely understood. In the striatum, where D receptors are abundant, antipsychotic medications may affect neural function in studies of animals, healthy volunteers, and patients, yet the relevance of this to pharmacotherapeutic actions remains unresolved. In this same brain region, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
0
16
1
Order By: Relevance
“…Previous research has suggested an influence of antipsychotic medication on striatal rCBF. 52,63,67,68 While we did not observe an association between striatal rCBF and antipsychotic dose, we cannot exclude a potential effect of antipsychotic medication. Thus, future studies should include nonmedicated patients and patients taking first-generation antipsychotics to generalize the relationship between apathy and striatal activity to these populations.…”
Section: Limitationscontrasting
confidence: 62%
“…Previous research has suggested an influence of antipsychotic medication on striatal rCBF. 52,63,67,68 While we did not observe an association between striatal rCBF and antipsychotic dose, we cannot exclude a potential effect of antipsychotic medication. Thus, future studies should include nonmedicated patients and patients taking first-generation antipsychotics to generalize the relationship between apathy and striatal activity to these populations.…”
Section: Limitationscontrasting
confidence: 62%
“…As expected in a heterogeneous syndrome such as schizophrenia and given the complex circuit-dependent actions of neurotransmitters, some studies (150,151), have demonstrated that individuals with treatment resistant schizophrenia, who may have persistent negative symptoms (16, 152), may have decreased dopamine synthesis capacity. This is further supported by recent evidence that phase of illness and antipsychotic medications may alter dopaminergic tone by increasing presynaptic dopamine capacity (153). As such, there may be heterogeneity in dopamine signaling pathways such that the underlying hyperdopaminergic state in subcortical regions, which was long thought to be the field's understanding of dopamine signaling in patients with schizophrenia (154), may only be present in a subgroup of patients.…”
Section: Inflammation Dopaminergic/ Glutamatergic Signaling and Rewmentioning
confidence: 86%
“…Results relating changes in rCBF in VS to improvement in symptoms were less consistent (table 1). 12 25 However, one investigation went on to demonstrate that this rCBF change in VS was associated with presynaptic dopamine synthesis capacity in the VS 12. Clearly striatal modulation is warranted and regulation of striatal dopamine has been described as an ascending, feedforward spiral of information flow (figure 2).…”
Section: Methodsmentioning
confidence: 99%